(untitled) (Reflection and Critique Law Magazine, 2022)
This article aims to outline a prognosis about fake news that surrounds the electoral process of, without pretending to elaborate a very deep analysis. To this end, it sought to gather the necessary background by delimiting the problem in terms of importance for the democratic political regime, as well as the technical and conceptual analysis of fraudulent information in the light of its evolution in the national political scenario. The method used was descriptive, with a qualitative approach, through a vast bibliographic review and content analysis. It is concluded that the phenomenon will find fertile ground to manifest its effects, causing serious damage to democracy.